A Collaborative Multi-Method Approach to Evaluating Indigenous Land-Based Learning With Men. (3rd March 2022) - Waddell-Henowitch, Candice; Gobeil, Jason; Tacan, Frank; Ford, Marti; Herron, Rachel V.; Allan, Jonathan A.; Kruth, Madeleine L.; Spence, Stephanie
In Canada, a vast majority of urban Indigenous people face distinct challenges accessing and connecting to Indigenous cultural practices. Research has found that colonial policies and practices continue to disrupt and fracture traditional methods of passing down cultural teachings, including dispossession from traditional lands in which cultural practices are rooted. This disruption continues to affect the availability of educational programming by and with Indigenous people and in Indigenous languages. This research involves a multi-method approach to observe and engage with a land-based traditional drum-making program for Indigenous men in an urban center in Southwestern Manitoba. By participating, watching, and listening to the men within the workshops through unstructured observation, Sharing Circles, individual interviews, and photovoice, we aim to understand the impacts of land-based learning on Indigenous men's well-being. The study is designed in accordance with University and Tri-Agency ethical guidelines, integrating ownership, control, access and possession (OCAP), as well as the principles of respect, relevance, reciprocity, and responsibility within all phases of the research. The research is co-created by the university researchers, community collaborators, and other relevant stakeholders.